Ultrasound-Promoted Synthesis of Spirocyclopropanes from Switchable Starting Materials via Azomethine Ylide [3+2]-Cycloaddition - Yavari, Issa; Sheikhi, Sara; Sheykhahmadi, Jamil; Taheri, Zohreh; Halvagar, Mohammad Reza (Synthesis, 2021)
An ultrasound-promoted green protocol to access a new series of spirocyclopropanes from indeno[1,2-b]quinoxaline derivatives and azomethine ylides, generated in situ from the iodine-catalyzed reaction of acetophenones as well as of 2-methylquinoline with pyridine in the presence of a base, is described. These transformations proceed via a spirocyclopropanation reaction followed by elimination of pyridine. Clear evidence for the structure of a spirocyclopropane-linked indenoquinoxaline derivative was obtained from single-crystal X-ray analysis. The most important feature of this reaction is the fact it forms three stereogenic centers, one of which is quaternary, with excellent selectivity.
Keywords: sonochemical synthesis; [3+2]-cycloaddition; spirocyclopropanes; azomethine ylides; iodine